ANALYSIS OF THE COMPETITIVENESS OF UKRAINIAN HEALTHCAREINSTITUTIONS IN THE CONTEXT OF THE SUSTAINABLE DEVELOPMENT ECONOMY - KAIDA, Oleh; KOSTIUK, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article reveals the importance of competitiveness of Ukrainian healthcare institutions in the context of the sustainable development economy, which determines their ability to adapt to changes and effectively respond to social challenges. It is determined that the integration of the principles of sustainable development, including economic, social and environmental sustainability, contributes to the long-term functioning of health care facilities and the provision of high-quality medical services. It is established that the key factors of competitiveness are financial stability, advanced training of medical personnel, and the introduction of innovative approaches to management and technological support. It is found that achieving the Sustainable Development Goals of Ukraine for the period up to 2030 requires comprehensive strategies that cover both public policy and internal reforms of health care institutions. Implementation of these strategies involves the use of new financing mechanisms, development of public-private partnerships, modernization of the material and technical base of healthcare facilities, and optimization of management processes. It is proven that raising the salaries of healthcare workers and providing additional social guarantees will help to retain professional staff and improve the quality of medical services. It is substantiated that the expansion of the autonomy of healthcare institutions through strategic documents, such as the Decree of the President of Ukraine No. 261/2021 dated 18.06.2021 and the Strategy for the Development of the Healthcare System until 2030, will help to increase their independence in decision-making and financial stability. This will allow healthcare institutions to actively implement innovations and provide quality healthcare. It is found that the digitalization of management processes, the introduction of uniform standards for the provision of medical services, and the development of a system of self-government for medical workers are important components of increasing the competitiveness of the healthcare sector. It is concluded that the competitiveness of health care institutions in the context of sustainable economic development directly depends on financial support, staff qualifications, management efficiency and the ability to implement modern technologies. Insufficient funding and a lack of strategic vision can limit the ability of healthcare facilities to adapt to an unstable economic environment. Therefore, a comprehensive approach to the development of the industry’s competitiveness is necessary to ensure its stable functioning and improve the quality of healthcare services for the population of Ukraine.